Influence of different dispersants on rheological behaviors of coal water slurry prepared from a low quality coal. Issue 56 (15th October 2019) - Hu, Shunxuan; Liu, Liming; Yang, Xin; Li, Junguo; Zhou, Baonan; Wu, Changning; Weng, Li; Liu, Ke
Abstract : To improve the efficiency of the gasification or combustion process of coal water slurry (CWS), it is significant to optimize the rheological properties and increase the solid concentration of CWS. Abstract : To improve the efficiency of the gasification or combustion process of coal water slurry (CWS), it is significant to optimize the rheological properties and increase the solid concentration of CWS. Particularly, preparing CWS from low quality coal remains a peculiarly intriguing subject due to the large reserve and low price of low quality coals in China and very successful industrial applications of CWS all over the world. In this work, refined coal particles were obtained by applying an improved fine particle flotation method on a low quality coal. The refined coal used for CWS preparation had a much lower ash content and higher calorific value than those of the raw coal, which could hardly be utilized for preparing a qualified CWS in basic fluidity. The CWS derived from the refined coal had a good fluidity, with apparent viscosity of 1045.75 mPa s and solid concentration >60 wt% in dispersant free conditions. The effects of dispersants i.e., Naphthalene Sulfonate Formaldehyde condensate (NSF), Polyoxyethylene Polycarboxylic Acid ether (PPA), and Sulfonated Melamine-Formaldehyde resin (SMF), and their dosages on the rheological characteristics of CWS prepared with the refined coal had been investigated. Experimental results showed that slurry ability for CWS was obviously improved by using the refined coal. This was due to the decrease in both the porosity and hydrophilicity of coal particles as confirmed by SEM and FT-IR analyses. The apparent viscosity of CWS was decreased by 30%–60% by adding one of those dispersants with a dosage of 0.6 wt%. Through observation of the rheological behaviors, the CWS samples generally behaved as a shear thinning fluid, and the measured viscosity was well correlated by the Herschel–Bulkley equation. The PPA dispersant exhibited the best performance on reducing the viscosity and yield stress among the dispersants in this study. It could be attributed to the best improvement in wettability of the coal surface and the largest decrease in surface tension of deionized water by PPA. The electrostatic force might have little contribution to viscosity reduction of CWS in this suspension.